Pemanfaatan Peta Desa dalam Mendorong Pembangunan Berbasis Data : Studi Program Kerja KKN di Desa Pangkil Kabupaten Bintan - Auliya Rahma; Azizah Rahmatul Amri; Hillyatul Aulia; Imelda Pandiangan; Tifani Cris Cahaya Kasih. S; Tiodorasi Simanjuntak; Ummu Rahmadhani; Veronica Yuliani Ginting; Yusnike Yusnike; Yudi Umara (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
This research is motivated by the need to improve the effectiveness of village development planning through participatory digital mapping technology. Pangkil Village, which is characterized by areas divided into three hamlets with various facilities, requires accurate spatial data as a basis for decision-making. The purpose of this study is to determine the impact of the application of digital mapping technology on increasing community participation and the quality of village planning. The method used was qualitative with data collection through participatory observation, in-depth interviews with village officials and residents, and analysis of digital map documents of Pangkil Village. The collected data were then processed and analyzed thematically to get a comprehensive picture of the implementation of the technology and the role of the community. The results showed that the use of digital mapping technology succeeded in increasing community involvement in the planning process because they could directly contribute to the data collection of areas and facilities. In addition, the quality of village planning is improved because village officials can make decisions based on valid and structured data. Increased participation also strengthens transparency and accountability in village development. Overall, this research proves that simple yet appropriate technology can empower village communities and improve development governance.